Pre-exposure prophylaxis (PrEP) efficacy to reduce HIV/AIDS incidence rate among male sex to male (MSM) in Asia - Prayogi Miura-Susanto (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
Human immunodeficiency virus (HIV) infection is a global epidemic, with the Asia-Pacific area as the second largest contributor of cases in the world. Men sex to men (MSM) are a key population in the epidemy. One strategy to control the incidence of HIV infection is the use of pre-exposure prophylaxis (PrEP). Until now, World Health Organization (WHO) recommended two drug combinations for use PrEP containing tenofovir disoproxil fumarate and emtricitabine (TDF/FTC), which can be taken daily or as needed (on-demand). PrEP is highly effective in preventing HIV infection among the MSM group. However, the use of PrEP in Asian countries is still very low.